Land Information System (LIS) for Land Administration and Management in Bangladesh (Journal of Bangladesh Institute of Planners, 2012)
Bangladesh has a very high population density. Scarce land and the rapid increase of population of the country are creating high pressure over land-man ratio. Land ownership record system is insufficient and incomplete in Bangladesh. As a result, it spills out jumbled and spontaneous land development throughout the country, especially in the major cities. In this situation, it is important to establish a compatible land administration and management system for establishing a systematic approach for planned land development. Land Information System (LIS) is the most accountable and feasible systematic approach for developing an up-to-date land administration and management. LIS is related to various quantitative and qualitative aspects of land resource. Holding different cartographic information, LIS facilitates capturing, retrieval, and querying of information and provides tools to perform different analyses. Based on the secondary information by literature review, this paper is aimed at studying the existing land administration system, and recommending feasible interventions and strategy of LIS for creating an efficient land administration and management policy for Bangladesh. This paper also focuses on the challenges of LIS that are needed to be resolved for framing the existing land administration and management policy for planned and controlled growth of Bangladesh.DOI: http://dx.doi.org/10.3329/jbip.v2i0.9572Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 116-125